Efektivitas Metode Preview, Question, Read, Summarize, and Test (PQRST) dalam Pembelajaran Fikih di Madrasah Ibtidaiyah - Mahsun Fais (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2023)
This study focuses on the application of the PQRST (Preview, Question, Read, Summarize, and Test) method in Fiqh learning in class V of Madrasah Ibtidaiyah (MI) Al Ikhlasul Hidayah. The methods that have been used in class tend to be conventional, where the material is taught through lectures, followed by memorization, and practice. This condition often causes students to feel bored, tired, and less interested in learning, which ultimately hinders the achievement of optimal learning outcomes. In this study, the approach used is classroom action research with qualitative methods, where data is obtained through observation and interviews. The results of the study showed that the application of the PQRST method in Fiqh learning in class V MI Al Ikhlasul Hidayah succeeded in increasing students' interest in learning. The learning process becomes more interesting, effective, and optimal, which in turn contributes to increasing students' understanding of the material and interest in Fiqh lessons.